RAILWAYS AND ITS IMPACT ON PUBLIC HEALTH IN COLONIAL BENGAL: A LITERARY OVERVIEW - Sarkar, Laboni (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In colonial Bengal, the advent of railways represented a transformative moment in both transportation infrastructure and socio-economic progress. The expansion of railways significantly facilitated the movement of people and goods, streamlining transportation. However, this heightened interconnectedness had its downsides, notably the increased transmission of diseases like malaria. The article conducts a thorough historical analysis through the lenses of literary traditions, exploring how railways altered settlement patterns, including the construction of embankments and dams, and influenced the interaction between humans and disease vectors. Drawing from government health reports, news accounts, and diverse perspectives, the article critically assesses the issues arising from borrow pits, embankments and dams. This comprehensive exploration contributes to a nuanced understanding of the environmental and health ramifications associated with major infrastructural changes implemented during the colonial era, providing valuable insights into historical contexts.